Effect of the multifunctional cosmetic ingredient sphinganine on hair loss in men and women with diffuse hair reduction - Gerlach N; Mentel M; Köhler T; Tuchscherer B; Garbe B; Ülker J; Tronnier H; Heinrich U; Farwick M (Dove Medical Press, 2016)
Nicole Gerlach,1,* Matthias Mentel,2,* Tim Köhler,2 Benjamin Tuchscherer,2 Birgit Garbe,1 Jasmina Ülker,1 Hagen Tronnier,1 Ulrike Heinrich,1 Mike Farwick2 1DermaTronnier GmbH & Co. KG, Institute for Experimental Dermatology, Witten/Herdecke University, Witten, 2Evonik Nutrition & Care GmbH, Essen, Germany *These authors contributed equally to this work Abstract: Sphingolipids are well known to promote keratinocyte differentiation and to induce ceramide production. In addition, they show anti-inflammatory and antimicrobial activities. Thus, the aim of this study is to investigate the potential effect of sphinganine on prolonging the hair anagen rate and improving the overall hair quality and scalp health. The inhibitory potential of sphinganine toward 5-α-reductase was studied using an in vitro assay. The stimulation of the antimicrobial peptide HBD2 by sphinganine was measured by real-time polymerase chain reaction and immunostaining. Sphinganine bioavailability was studied ex vivo using a pig skin model. A placebo-controlled, double-blind study was designed to evaluate the efficacy of sphinganine on hair loss and hair/scalp quality in vivo. In vitro results showed that sphinganine is a potent inhibitor of 5-α-reductase type I that prevents the conversion of testosterone to dihydrotestosterone, a key factor of androgenetic male baldness. In vivo results demonstrated efficacy in reducing non-illness-related hair loss among males. In terms of expert rating, all hair quality and scalp parameters improved after application of sphinganine. Improved scalp health might be linked to the observed increase of the antimicrobial peptide HBD2. Thus, sphinganine is well suited as a topical alternative for the improvement of scalp health and hair quality and anti-hair loss application. Keywords: sphinganine, 5-α-reductase inhibition, HBD2, hair loss, anagen rate, TrichoScan®